1987
DOI: 10.1080/09553008714551381
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Carcinogenesis in Different Rat Strains after Irradiation and Hormone Administration

Abstract: Radiation carcinogenesis of the rat mammary gland was investigated with the objective of investigating the combined effect of oestrogen administration and irradiation. Three rat strains, Sprague-Dawley, Wistar WAG/Rij and Brown Norway, with different susceptibilities to the induction of mammary cancer, have been irradiated with X-rays and mono-energetic neutrons. Increased hormone levels were obtained by subcutaneous implantation of pellets with oestradiol-17 beta (E2). The tumour incidence results were correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Radiation and estrogens, namely 17~-estradiol (E2) or DES, were reported to exert either an additive [72] or a synergistic effect [73,74]. The effect of E 2 administration and irradiation on mammary tumorigenesis is equal for hormone administration 1 week before, or beginning 12 weeks after irradiation [72]. This additive effect of hormone administration and irradiation was not evident if the hormone was administered beginning 24 weeks after irradiation.…”
Section: Rat Mammary Tumors 11mentioning
confidence: 94%
See 2 more Smart Citations
“…Radiation and estrogens, namely 17~-estradiol (E2) or DES, were reported to exert either an additive [72] or a synergistic effect [73,74]. The effect of E 2 administration and irradiation on mammary tumorigenesis is equal for hormone administration 1 week before, or beginning 12 weeks after irradiation [72]. This additive effect of hormone administration and irradiation was not evident if the hormone was administered beginning 24 weeks after irradiation.…”
Section: Rat Mammary Tumors 11mentioning
confidence: 94%
“…The latency period for tumor development is shortened considerably in estrogen-treated rats; there is an increase in the number of rats with carcinomas, especially cribriform carcinomas [18], and in the number of tumors/tumor-bearing rat [71]. Radiation and estrogens, namely 17~-estradiol (E2) or DES, were reported to exert either an additive [72] or a synergistic effect [73,74]. The effect of E 2 administration and irradiation on mammary tumorigenesis is equal for hormone administration 1 week before, or beginning 12 weeks after irradiation [72].…”
Section: Rat Mammary Tumors 11mentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to epilepsy research, WAG rats are widely used in cancer research, including studies on gamma irradiation on induction of mammary carcinoma [49, 50]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies on mammary tumourigenesis, performed at TNO in three rat strains, notably Sprague-Dawley, WAG/Rij and BN/BiRij, have shown that only in WAG/Rij rats was an appreciable number of carcinomas induced by irradiation ( . Earlier analysis of the TNO results (Broerse et al 1983) was based on the excess actuarial incidence at an age of 22 months or on the forward shift in time. For the incidence of fibroadenomas in WAG/Rij rats, the exponent of the dose-effect curve for excess actuarial incidence after irradiation with 0-5 MeV neutrons was also lower than 1.…”
Section: Nature Of Dose-response Relationshipsmentioning
confidence: 99%